2021
DOI: 10.21511/imfi.18(2).2021.04
|View full text |Cite
|
Sign up to set email alerts
|

Ownership composition and intellectual capital disclosure: Indonesia as a case study

Abstract: This study explores whether ownership structure (comprising ownership concentration, foreign, managerial, and institutional ownership) affects intellectual capital disclosure (ICD) in Southeast Asia’s largest stock market and Indonesia’s emerging economy. The sample includes 323 public firms listed on the Indonesia Stock Exchange (IDX) from seven industries between 2008 and 2017, or 2,634 firm-year observations. Data were analyzed using the ordinary least squares (OLS) regression with robust standard errors. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 34 publications
5
13
0
Order By: Relevance
“…Hypothesis one predicts that board nationality does not have a significant impact on ICD; however, based on the finding of the study, we, therefore, reject the null hypothesis. The finding concurs with those of Rasmini et al (2014) and Othman et al (2018), but contradicts that of Ulfah et al (2021).…”
Section: Variablessupporting
confidence: 89%
See 1 more Smart Citation
“…Hypothesis one predicts that board nationality does not have a significant impact on ICD; however, based on the finding of the study, we, therefore, reject the null hypothesis. The finding concurs with those of Rasmini et al (2014) and Othman et al (2018), but contradicts that of Ulfah et al (2021).…”
Section: Variablessupporting
confidence: 89%
“…The multiple regression results revealed that the presence of foreign directors on the board had a significant impact on the extent of innovation capital disclosure. However, using data from annual reports of 323 Southeast Asia's largest stock market and Indonesia's emerging economy during the period 2008 to 2017, Ulfah et al (2021) found that foreign ownership had a negative and significant impact on ICD of Indonesian firms. In view of the foregoing, the following hypothesis is formulated:…”
Section: Board Nationality and Intellectual Capital Disclosurementioning
confidence: 99%
“…According to Krippendorff (1980), content analysis derives reproducible and accurate conclusions from data based on their context. This approach is widely acknowledged as impartial and dependable and is mostly employed to investigate intellectual and human capital disclosure (Ulfah et al, 2021;Kusumawardani et al, 2021a). Furthermore, Larran Jorge et al ( 2016) stated that content analysis reduces questionnaire and interview deficiencies (Larran Jorge et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…As a result, outside shareholders do not need additional monitoring of manager behavior. Several studies have proven the negative influence of management's share ownership on intellectual capital disclosure (Ahmed Haji, 2015;Al-Sartawi, 2018;Haji & Ghazali, 2013;Rahman, Sobhan, & Islam, 2019;Ulfah, Yudaruddin, & Yudaruddin, 2021). Meanwhile, an investigation conducted by Hidalgo, García-Meca, and Martínez (2011); Juhmani (2013), andAlfraih (2018) showed that there is no relationship between management shareholding and disclosure of intellectual capital.…”
Section: Introductionmentioning
confidence: 99%
“…Institutional ownership promotes management to disclose intellectual capital as widely as possible. The high number of shares owned by the institution will result in higher disclosure of intellectual capital (Juhmani, 2013;Mukti & Istianingsih, 2018;Ulfah et al, 2021). However, the results do not always match this logic, as shown by Rahman et al (2019) who reported that more institutional share ownership would reduce the quantity of intellectual capital disclosed.…”
Section: Introductionmentioning
confidence: 99%